MIGRATORY MOBILITY IN THE RURAL AREAS OF KARACHAY-CHERKESS REPUBLIC - Irina Vladimirovna Chernova (Наука. Инновации. Технологии)
In the article it is shown migration situation in the countryside of Karachay-Cherkessia in 1965-2009 gg. And Displayed evolution of migratory indicators as a whole on the subject, and at the level of administrative districts.